Secondary paroxysmal dyskinesia in multiple sclerosis: Clinical–radiological features and treatment. Case report of seven patients. (November 2017) - Ciampi, Ethel; Uribe-San-Martín, Reinaldo; Godoy-Santín, Jaime; Cruz, Juan Pablo; Cárcamo-Rodríguez, Claudia; Juri, Carlos
Secondary paroxysmal dyskinesias (SPDs) are short, episodic, and recurrent movement disorders, classically related to multiple sclerosis (MS). Carbamazepine is effective, but with risk of adverse reactions. We identified 7 patients with SPD among 457 MS patients (1.53%). SPD occurred in face ( n = 1), leg ( n = 2), or arm +leg ( n = 4) several times during the day. Magnetic resonance imaging (MRI) showed new or enhancing lesions in thalamus ( n = 1), mesencephalic tegmentum ( n = 1), and cerebellar peduncles ( n = 5). Patients were treated with clonazepam and then acetazolamide ( n = 1), acetazolamide ( n = 5), or levetiracetam ( n = 1) with response within hours (acetazolamide) to days (levetiracetam). No recurrences or adverse events were reported after a median follow-up of 33 months.